2019
DOI: 10.15761/mca.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic (Helminthic) cardiomyopathy: A review and pooled analysis of pathophysiology, diagnosis and clinical management

Abstract: Neglected tropical diseases form an important component of the burden of cardiac disease in resource-constrained countries. Some diseases resulting from infection by helminthic parasites such as endomyocardial fibrosis, schistosomiasis and hookworm infections are part of the neglected tropical diseases. The neglect has contributed to the under-appreciation and under-research of helminthic cardiac diseases. In contrast, infections by helminthic parasites are prevalent in resource-constrained countries and are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 115 publications
(229 reference statements)
0
2
0
1
Order By: Relevance
“…O envolvimento miocárdico ou pericárdico por espécies de Schistosoma é raro e pode ocorrer devido ao acúmulo de ovos de Schistosoma, que induzem uma resposta granulomatosa local. 6 No único caso publicado na literatura médica, 3 o estudo histopatológico do pericárdio mostrou espessamento fibroso com aumento do tecido conjuntivo e identificou a presença de ovos do Schistosoma haematobium. No nosso caso, o estudo anatomopatológico de fragmentos do pericárdio mostrou tecido fibroconjuntivo exibindo extensa calcificação distrófica, contudo não identificou ovos do Schistosoma mansoni.…”
Section: Discussionunclassified
“…O envolvimento miocárdico ou pericárdico por espécies de Schistosoma é raro e pode ocorrer devido ao acúmulo de ovos de Schistosoma, que induzem uma resposta granulomatosa local. 6 No único caso publicado na literatura médica, 3 o estudo histopatológico do pericárdio mostrou espessamento fibroso com aumento do tecido conjuntivo e identificou a presença de ovos do Schistosoma haematobium. No nosso caso, o estudo anatomopatológico de fragmentos do pericárdio mostrou tecido fibroconjuntivo exibindo extensa calcificação distrófica, contudo não identificou ovos do Schistosoma mansoni.…”
Section: Discussionunclassified
“…The myocardial and pericardial involvement of SM species is rare and can occur due to the accumulation of SM eggs, which induce a local granulomatous response. 6 In the only case published in the medical literature, 3 the histopathological study of the pericardium showed a fibrous thickening with an increase in the connective tissue and identified the presence of Schistosoma haematobium eggs. In the present case, the anatomopathological study of pericardial fragments showed fibrous connective tissue, showing extensive dystrophic calcification, but no SM eggs were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae of T. spiralis are unable to encyst in other types of cells including myocardial muscle cells. The cardiac pathology during trichinosis is due to the anti-Trichinella immune response that results in eosinophilic myocarditis [4] .…”
Section: Introductionmentioning
confidence: 99%